Room-temperature air oxidation of organic pollutants via electrocatalysis by nanoscaled Co-CoO on graphite felt anode. (October 2019) - Sun, Min; Zhang, Yu; Liu, Hui-Hui; Zhang, Feng; Zhai, Lin-Feng; Wang, Shaobin
Abstract: Oxygen (O2 ) in air is an eco-friendly and economical oxidant. However, its activation is an energy-intensive process requiring high operation temperature. Herein, we report the synthesis of nanoscaled Co-CoO on a graphite felt (GF) as an anode material for electrocatalytic wet air oxidation (ECWAO) of water contaminants at room temperature. Such an ECWAO process shows extensive effectiveness in mineralizing a variety of biorefractory organic pollutants. A probe pollutant, bisphenol A (BPA), is rapidly degraded in 180 min with mineralization efficiencies higher than 85% over a wide pH range from 3.0 to 11.0. The Co-CoO/GF electrode exhibits excellent stability in the ECWAO process, without loss of activity and leaching of metal. The ECWAO process is confirmed to be initiated by the electrochemical activation of O2 through a non-radical pathway. The CoO on the surface of Co nanoparticle is identified as the catalytically active site, at which O2 molecules are first converted to chemisorbed oxygen species and then electrochemically oxidized to their activated states. The ECWAO process with the Co-CoO/GF electrode presents the merits of high efficiency, low energy input and environmental friendliness, and has a great potential for practical wastewater treatment. Highlights: An electrocatalytic wet air oxidation (ECWAO) of water contaminants was achieved. Co@CoO on graphitic felt demonstrates high activity and stability in ECWAO. ECWAO is triggered by activation of O2 through a non-radical pathway. CoO is the active site for O2 activation to induce electro-oxidation reaction.